Growth and Yield of Sweet Corn (Zea mays var. Saccharata Sturt.) in Response to the Application of Inorganic Calcium Nitrate Fertilizer - Mulyana, Erik (Departemen Agronomi dan Hortikultura, 2025)
Sweet corn is a horticultural commodity that is widely cultivated in Indonesia. This experiment aimed to determine the effectiveness of inorganic calcium nitrate fertilizer on the growth and yield of different sweet corn plants (Zea mays var. Saccharata Sturt.). The study was conducted at the Sindangbarang Experimental Field, Bogor, West Java. This experiment used a randomized complete block design (RCBD) with a single factor, namely the dose of fertilizer application. The treatment consisted of one factor with six levels of fertilization, namely (P1) control, (P2) standard NPK (135 kg N ha-1, 72 kg P₂O₅ ha-1, and 120 kg K₂O ha-1), (P3) 0.5 dose of calcium nitrate fertilizer, (P4) 0.75 dose of calcium nitrate fertilizer, (P5) 1.0 dose of calcium nitrate fertilizer, and (P6) 1.5 dose of calcium nitrate fertilizer. The test results showed that the treatment of applying 0.5 – 1.5 dose of calcium nitrate fertilizer is higher increased stover weight, cob weight with husked, cob weight without husked, production and productivity which were statistically higher than the control treatment. The application of 0.5 dose of calcium nitrate fertilizer has the highest Relative Agronomic Effectiveness (RAE) value that meets the requirements to pass the fertilizer effectiveness test, with an RAE value of 95%. Keywords: fertilizer effectiveness, horticulture plants, nutrient, productivity